(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The blockchain ecosystem meets the GDPR in the healthcare sector, where its impact is widely debated. To debunk the narrative of contrast, a complexity of applications is displayed, and the legal background is outlined, introducing the matter of governance and compliance with GDPR principles, rights and obligations. Although this work cannot dispel the uncertainties in the application of GDPR rules to blockchains, such as the one regarding the right to erasure, and given the issues elected for further study, we focus on the room for compliance arising from the diverse potential of this technology, which can be shaped according to different architectural choices.Â Â